The development of the expressive speech after surgery in Broca’s area in two-year-old child: а case report - S. L. Moiseeva; T. Hartlieb; P. Winkler; M. Kudernatsch; M. Staudt (Русский журнал детской неврологии)
The case history of a two-year-old child with meningo-angiomotosis of the left frontal lobe is described in this article. The special features of the clinical manifestations were two episodes of nonconvulsive status epilepticus and absence of seizures between these episodes. The diagnosis was suspected at the age of 14 months after magnetic resonance imaging investigation. The presurgical investigation/diagnostics before the neurosurgery and the neurosurgery were performed in the Department for Children’s Neurology of Schoen Klinik Vogtareuth (Germany). The results of electroencephalographic video monitoring over 7 days showed derangements in the left fronto-central and temporo-parietal regions. The repeated magnetic resonance imaging showed no progression of tumor growth. At the age of 2 years and 4 months the girl had been operated. A subtotal lobectomy was carried out. The patient showed a positive trend of speech development after the operation. The question of a lateralization of speech center after surgery in Broca’s area is debated in this article.